Protective effect of Rhei Rhizoma on reflux esophagitis in rats via Nrf2-mediated inhibition of NF-κB signaling pathway. Issue 1 (December 2015) - Kwon, O; Choo, Byung; Lee, Joo; Kim, Min; Shin, Sung; Seo, Bu-Il; Seo, Young-Bae; Rhee, Man; Shin, Mi-Rae; Kim, Gyo-Nam; Park, Chan; Roh, Seong-Soo
Abstract Background Rhei Rhizoma has been widely used as a traditional herbal medicine to treat various inflammatory diseases. The present study was conducted to evaluate its anti-inflammatory activity against experimental reflux-induced esophagitis (RE) in SD rats. Methods Rhei Rhizoma was administered at 125 or 250 mg/kg body weight per day for 7 days prior to the induction of reflux esophagitis, and its effect was compared with RE control and normal rats. Results Rhei Rhizoma administration markedly ameliorated mucosal damage on histological evaluation. The elevated reactive oxygen species in the esophageal tissue of RE control rats decreased with the administration of Rhei Rhizoma. RE control rats exhibited the down-regulation of antioxidant-related proteins, such as nuclear factor-erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) expression levels, in the presence of esophagitis; however, the levels with Rhei Rhizoma treatment were significantly higher than those in RE control rats. Moreover, RE control rats exhibited the up-regulation of protein expressions related to oxidative stress in the presence of esophagitis, but Rhei Rhizoma administration significantly reduced the expression of inflammatory proteins through mitogen-activated protein kinase (MAPK)-related signaling pathways. The protein expressions of inflammatory mediators and cytokines by nuclear factor-kappa B (NF-κB) activation were modulated through blocking the phosphorylation of inhibitor of nuclear factor kappa B (IκB)α. Conclusion Our findings support the therapeutic evidence for Rhei Rhizoma ameliorating the development of esophagitisvia regulating inflammation through the activation of the antioxidant pathway.